THE INFLUENCE OF NEW WAVE MARKETING 5A ON CONSUMER DECISIONS (Consumer Behavior Study at PT. Pegadaian Syariah, Lhokseumawe City Branch) - Fini Nurul Azzara; Adnan; Ikramuddin; Chalirafi (RADJA PUBLIKA, 2025)
This research aims to determine the influence of Aware, Appeal, Ask, Act and Advocate on consumer decisions (Consumer Behavior Study at PT. Pegadaian Syariah Lhokseumawe City Branch). The method used in sampling is Non-Probability sampling actendal fiber sampling. With a total of 105 respondents. Primary data in this research was taken through interviews and distributing questionnaires. The data analysis technique used is the multiple linear regression analysis method with the help of the SPSS version 26 program. The results of this test show simultaneously that Appeal and Act have a positive and significant effect on consumers' decisions to pawn gold in the city of Lhokseumawe, but the variables Aware, Ask and Advocate have no effect. on consumers' decisions to pawn gold in Lhokseumawe City. Partial Test, Aware has a positive and insignificant influence on consumer decisions, Appeals has a positive and significant influence on consumer decisions, Asking has a negative and significant influence on consumer decisions, Actions have a positive and significant influence on consumer decisions, then Advocates have a negative influence on consumer decisions to pawn city gold Lhokseumawe. The managerial implications in this research show that increasing Awareness, Appeal and Act on consumers' decisions to pawn gold in Lhokseumawe city. Gold pawning must utilize Aware, Appeal and Act, meaning that the higher the Aware, Appeal and Act, the higher consumer satisfaction with Lhoseumawe City gold pawning products.